Information Seeking Behavior of the Authors Sang Patriot Pierre Tendean’s Book - Fiona Alifa; Siti Maryam (Librarianship in Muslim Societies, 2022)
Information seeking behavior is one of the interesting topics to be studied so far. Everyone has different information seeking behavior, it is influenced by several factors, such as age, profession, gender, education, beliefs, living environment and so on. This article will discuss the results of research on the information seeking behavior of the authors of a book entitled The Patriot Pierre Tendean. The authors of the book consist of 7 (seven) people and they have different professional backgrounds, some are journalists, teachers, employees, doctors, entrepreneurs, housewives, and travelers. The main purpose of this study was to determine the information seeking behavior of the authors of the book. Besides that, it is also to find out the purpose of writing the book, as well as explore various supporting factors and inhibiting factors faced by the authors in finding the information they need. This study used a qualitative method with a phenomenological approach, and the required data were obtained through in-depth interviews with informants. The informants are six of the seven authors of the book The Patriot Pierre Tendean. The results showed that the information seeking behavior of the six authors had different stages, some were in accordance with Ellis' information seeking behavior model, and some used the Khulthau information search model. Meanwhile, the purpose of writing the book Sang Patriot Pierre Tendean is to provide a book that provides complete and accurate information about Pierre Tendean as one of the revolutionary heroes who died in the events of the September 30th Movement/PKI (G30S/PKI) in 1965. The inhibiting factor faced by these writers was related to licensing to obtain the information they needed, while the supporting factor was their high motivation and enthusiasm in seeking information to meet their needs in completing the writing of the book Sang Patriot Pierre Tendean